Structural Changes in Hippocampal Subfields in Major Depressive Disorder: A High-Field Magnetic Resonance Imaging Study - Huang, Yushan; Coupland, Nicholas J.; Lebel, R. Marc; Carter, Rawle; Seres, Peter; Wilman, Alan H.; Malykhin, Nikolai V. (Biological psychiatry (1969), 2013)
Magnetic resonance imaging (MRI) has shown lower hippocampal volume in major depressive disorder (MDD). Preclinical and postmortem studies show that chronic stress and MDD may affect hippocampal subfields differently, but MRI spatial resolution has previously been insufficient to measure subfield volumes. Twenty MDD participants (9 unmedicated and 11 medicated, both>6 months) and 27 healthy control subjects were studied. We used T2-weighted two-dimensional fast spin echo and T1-weighted three-dimensional magnetization prepared rapid acquisition gradient-echo sequences at 4.7 T to compare hippocampal subfield volumes at .09 μL voxel volume. Unmedicated MDD participants had a lower dentate gyrus volume than control subjects or medicated MDD participants and a lower cornu ammonis (CA1–3) volume in the hippocampal body subregion than control subjects. Hippocampal volumes in unmedicated MDD showed evidence of localization to specific subfields and subregions, findings that appear, on the surface, consistent with preclinical evidence for localized mechanisms of hippocampal neuroplasticity. Strengths include in vivo measurement of entire hippocampal subfields and separation between unmedicated and medicated MDD. Limitations include power to control for multiple comparisons and that MRI landmarks approximate the subfields defined by cellular microstructure.